MOVIMENTOS FORMATIVOS E POLÍTICOS DA GESTÃO DE EDUCAÇÃO ESPECIAL NO ESTADO DO ESPÍRITO SANTO - Vieira, Islene da Silva (2020)
This research aims to collaborate, by means of collaborative-critical action research, with the formative pathway of a group of public managers of Special Education in the State of Espírito Santo, in a perspective of communicative rationality. Using the p